Primerjava metodologij OOAD in OOSE za razvoj informacijskega sistema - Črv, Milan (Uporabna informatika (Ljubljana), 1997)
Object-oriented information systems development helps understanding the problem domain better, and building the application easier. Many object-oriented analysis and design methodologies have been published. Upon close examination, their similarities may be greater than their differences. Although the basic techniques are the same, each methodologist has a habit of altering them, introducing some new modelling concepts and a new notation. This paper introduces two popular methodologies (OOAD and OOSE) and sets out to identify the main similarities and differences between them.
Keywords: informacijski sistemi; metodologija; razvoj